Development of a non-alcoholic steatohepatitis model with rapid accumulation of fibrosis, and its treatment using mesenchymal stem cells and their small extracellular vesicles - Takayuki Watanabe; Atsunori Tsuchiya; Suguru Takeuchi; Shunsuke Nojiri; Tomoaki Yoshida; Masahiro Ogawa; Michiko Itoh; Masaaki Takamura; Takayoshi Suganami; Yoshihiro Ogawa; Shuji Terai (Regenerative Therapy, 2020)
Introduction: Currently, there are no approved drugs for treating non-alcoholic steatohepatitis (NASH); however, mesenchymal stem cells (MSCs) and their small extracellular vesicles (sEVs), which possess immunomodulatory activities, are potential candidates. This study aimed to develop a mouse model of NASH with rapid accumulation of fibrosis using the pre-established melanocortin type-4 receptor knockout (Mc4r-KO) NASH mouse model and lipopolysaccharide (LPS), and to evaluate the therapeutic effect of MSCs and their sEVs. Methods: Mc4r-KO mice (8 weeks old, male) were fed a western diet (WD) for 8 weeks. Next, the mice were intraperitoneally injected with lipopolysaccharide (LPS) twice a week for 4 weeks while continuing the WD. To confirm the therapeutic effect of MSCs and sEVs, human adipose tissue-derived MSCs or their sEVs were administered 12 weeks after initiation of the WD, and serum testing, quantitative analysis of fibrosis, and quantitative reverse transcription-polymerase chain reaction qRT-PCR were performed. Results: By providing a WD combined with LPS treatment, we successfully developed a NASH model with rapid accumulation of fibrosis. Both human MSCs and their sEVs decreased serum alanine transaminase levels and inflammatory markers based on qRT-PCR. Histological analysis showed that MSC or sEV treatment did not affect fat accumulation. However, an improvement in fibrosis in the groups treated with MSCs and their sEVs was observed. Furthermore, after administering MSCs and sEVs, there was a significant increase in anti-inflammatory macrophages in the liver. Conclusion: We successfully developed a NASH model with rapid accumulation of fibrosis and confirmed the anti-inflammatory and anti-fibrotic effects of MSCs and their sEVs, which may be options for future therapy.